Austrian Constitution and International Law - E. A. Vodyanitskaya (Московский журнал международного права, 2009)
The most important legal institution concerning Austria’s peaceful relations with other States is its status as a permanently neutral state which was declared unilaterally by Austria in 1955 by adopting the constitutional bill on permanent neutrality. After the accession to the EU Austria confirmed to accept the rights and obligations within the Union and its institutional framework, in particular the principles and the political goals of the EU. Austria’s accession to the EU constituted the most important transferof jurisdiction in the history of the Federal Constitution. On this occasion the Austrian legislature passed an amendment to the Federal Constitution which provides for the participation of Austrian organs in the decision-making process of the European Union.First of all, provisions on the election of Austrian members to the European Parliament were introduced by the amendment into the Constitution. Secondly, the amendment contains a procedure for participation of the Austrian lands and local governments in the decisions of the European Union. Thirdly, the legislative bodies on the central government level (National Council and Federal Council) are also accorded the right to participate in decision-making of the EU. Finally, a special provision confirming Austria’s participation in the Common Foreign and Security Policy of the Union was introduced.